Determinant factor for poverty alleviation on women entrepreneurship - Nik Syuhailah Nik Hussin; Zuraimi Abdul Aziz; Mohd Rafi Yaacob; Nik Madeeha Nik Mohd Munir; Siti Fariha Muhamad (2015)
Poverty reduction became a major objective in of improving the socioeconomic. It has becomes main targets and attention at many developing and developed countries. The Government continued to play the leading role in poverty eradication efforts by promoting income-generating projects, providing amenities to improve the quality of life and implementing program to inculcate positive values among the poor. The objective of this research is to find out the determinantfactors towards to poverty alleviationfor women entrepreneurship. The respondents in this study consisted of 300 women entrepreneurs who were running the business within three selected states in Malaysia. Data analyses were conducted using SPSS 20.0. The finding indicated that microfinance had a most significant relationship with poverty alleviation. In a nutshell, it was pointed that microfinance program is becoming more significant as the main contributor in creating new job opportunities and generating income for increasing social wellbeing and economic status of the poor and eradicating poverty.